Single-stranded loops as end-label polarity markers for double-stranded linear DNA templates in atomic force microscopy - Billingsley, Daniel J. (Oxford University Press, 2012)
Visualization of DNA–protein interactions by atomic force microscopy (AFM) has deepened our understanding of molecular processes such as DNA transcription. Interpretation of systems where more than one protein acts on a single template, however, is complicated by protein molecules migrating along the DNA. Single-molecule AFM imaging experiments can reveal more information if the polarity of the template can be determined. A nucleic acid-based approach to end-labelling is desirable because it does not compromise the sample preparation procedures for biomolecular AFM. Here, we report a method involving oligonucleotide loop-primed synthesis for the end labelling of double-stranded DNA to discriminate the polarity of linear templates at the single-molecule level. Single-stranded oligonucleotide primers were designed to allow loop formation while retaining 3′-single-strand extensions to facilitate primer annealing to the template. Following a DNA polymerase extension, the labelled templates were shown to have the ability to form open promoter complexes on a model nested gene template using two Escherichia coli RNA polymerases in a convergent transcription arrangement. Analysis of the AFM images indicates that the added loops have no effect on the ability of the promoters to recruit RNA polymerase. This labelling strategy is proposed as a generic methodology for end-labelling linear DNA for studying DNA–protein interactions by AFM.